The Effect of Competence and Compensation of Early Childhood Teachers on the Performance of Early Childhood Teachers in the City of Pematang Siantar - Rotua Herriay Maria Simangunsong; Prista Tarigan; Noor Sembiring (DINASTI RESEARCH, 2021)
Educational institutions need teachers who are competent or capable of teaching and carrying out their duties as educators and able to manage their work as well as possible in order to achieve the desired results for students. Compensation is an important factor and a challenge for many organizations to maintain and attract human resources. Different organizations compete for quality human resources because the quality of work is determined by the skills of its human resources. This reason causes many organizations to devote relatively large funds to developing their human resources so that they have the skills that match their needs. All teachers are entitled to a good income, including honorary and non-PNS teachers, including salary and allowances. Article 14 of the law on teachers and lecturers stipulates that all teachers are entitled to a decent income above the minimum subsistence. Providing fair and proper compensation will improve teacher performance so that they can carry out their duties properly.